Sparky's excellent misadventures my A.D.D. journal (by me, Sparky) - Carpenter, Phyllis; Ford, Marti; Horjus, Peter (Washington, D.C. Magination Press, 2000)
A young boy writes in his journal about the frustrations and triumphs of living with attention deficit disorder.
Ages 5-11"--cover p. [4].
Keywords: Attention-deficit hyperactivity disorder -- Fiction; Diaries -- Fiction